Determinants of ADR returns before and after domestic stock seasoned equity offerings: evidence from Asian and Latin American emerging markets - Lee, Chien-Chiang; Chen, Mei-Ping; Li, Chun-An; Chang, Chi-Hung (Journal of Business Economics and Management, 2011)
This paper examines the critical determinants of American depository receipt (ADR) returns before and after domestic stock seasoned equity offerings (SEOs) for Asian and Latin American emerging economies during 1990–2007, which has never been probed in related issues. We employ the Time Series Cross Section Regressions and General Method of Moments methods to document that domestic stock returns play a vital role in explaining Latin American ADR returns, while US investor sentiment is crucial in explaining Asian ADR returns. Local investor sentiment is found to be considerably important than domestic stock returns in Asian ADR returns, while Latin American local investor sentiment (US investor sentiment) is more important before (after) domestic stock SEOs. The results do not support the view that ADR-reconciled earnings per share (EPS) and stock EPS provide significant information to explain ADR returns in Latin American and Asian emerging markets both before and after SEOs. Furthermore, international market differences in a specific geography should be considered when diversifying investments and efficiency accounting communication with accounting convergence does not need to be emphasized. Article in English. Depozitorinių pakvitavimų pasiskirstymas: Azijos ir Lotynų Amerikos rinkose Santrauka. Nagrinėjami pagrindiniai Amerikos depozitoriumo pakvitavimų (ADR) grąžinimai, apimantys 1990–2007 metų laikotarpį. Straipsnio autoriai tai traktuoja kaip iki šiol netirtą reiškinį, nes analizuojamos dvi skirtingos rinkos – Azijos ir Lotynų Amerikos. Pasirinktu periodu šiose rinkose buvo jaučiamas ekonominis pakilimas. Straipsnio autoriai taiko laiko eilutės regresijos ir bendrąjį fiksuoto momento metodą. Tyrimo rezultatai parodė, kad yra tam tikrų skirtumųne tik tarp regionų, bet ir tarp atskirų investuotojų bei jų susiformavusių požiūrių į šias rinkas. Pažymima, kad turi būti įvertinami tiek rinkos, tiek geografiniai skirtumai difersifikuojant investicijas. Reikšminiai žodžiai: Amerikos depozitoriumo pakvitavimai, apskaitos informacija, investicijos, investuotojų požiūriai.